2008
DOI: 10.1159/000161113
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Changes Involved in Prolactin Secretion Induced by Mifepristone and Naloxone during Late Pregnancy

Abstract: Background/Aims: The antiprogesterone mifepristone facilitates prolactin release, an effect enhanced by administration of the opioid antagonist naloxone. The present study explores ultrastructural changes in lactotropes after mifepristone and naloxone administration, correlating them with the expression of pituitary prolactin. Methods/Results: Rats were sacrificed at 18:00 h on day 19 of pregnancy. Prolactin immunoelectron microscopy of lactotropes from control rats showed characteristics of quiescent cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
1
4
0
1
Order By: Relevance
“…The increased PRLR long mRNA content, if paralleled by an increase in the receptor protein, may also be a stimulus for induction of TH by the elevated PRL, counteracting the effect of P 4 decline. Although it has been shown that TIDA neuron responsiveness to PRL, measured as STAT5 activation [10], is decreased at the end of pregnancy and during lactation, accompanied with decreased TH expression [32,34], comparison of our results with those of Gabutti et al [47] may indicate that some degree of sensitivity to PRL is maintained. However, we found increased expression of SOCS family members mRNA after P 4 fall, confirming the results obtained by Steyn et al [9] using a different experimental model of P 4 withdrawal.…”
Section: Discussionsupporting
confidence: 44%
“…The increased PRLR long mRNA content, if paralleled by an increase in the receptor protein, may also be a stimulus for induction of TH by the elevated PRL, counteracting the effect of P 4 decline. Although it has been shown that TIDA neuron responsiveness to PRL, measured as STAT5 activation [10], is decreased at the end of pregnancy and during lactation, accompanied with decreased TH expression [32,34], comparison of our results with those of Gabutti et al [47] may indicate that some degree of sensitivity to PRL is maintained. However, we found increased expression of SOCS family members mRNA after P 4 fall, confirming the results obtained by Steyn et al [9] using a different experimental model of P 4 withdrawal.…”
Section: Discussionsupporting
confidence: 44%
“…A return to normal size between the first week and 6 months postpartum has been described [4,5]. Furthermore, an alteration of pituitary function by some drugs, which are frequently applied in late pregnancy, was found [13]. In postmenopausal women, cranio-caudal diameters were found to be significantly larger in individuals with estrogen substitution, compared to no substitution [7].…”
Section: Discussionmentioning
confidence: 99%
“…2b). Two-way ANOVA analysis was as follows: Drug factor (SAL, NAL) F Experiment 2: effect of progesterone, estrogen and NAL on prolactin secretion in stressed rats We previously showed that 5 mg/kg [11,14] or 10 mg/kg [7,8] Mp treatment 10 or 12 h before NAL administration induced prolactin secretion, while 2 mg/kg treatment did not. The present study used a 2 mg/kg Mp dose so no changes in prolactin secretion after SAL or NAL administration were expected.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Mp inhibits the hypothalamic dopaminergic neuronal system [11], the main inhibitory factor of prolactin secretion in terms of dopaminergic transmission and tyrosine hydroxylase (TH) expression [12,13]. This effect enables a significant activation of lactotrophs and primes the pituitary for a subsequent stimulatory action of NAL [14].…”
Section: Introductionmentioning
confidence: 99%